In Girum Imus Nocte et Consumimur Igni - The Situationist International (1957-1972) - Exhibition. In Girum Imus Nocte et Consumimur Igni - The Situationist International (1957-1972) (1). Exhibition. In Girum Imus Nocte et Consumimur Igni : The Situationist International (1957-1972) (2). Centraal Museum Utrecht. Museum Tinguely Basel. 2006-12-14. 2007-04-04. 2007-03-11. 2007-08-05; Agamben, Giorgio; Apostolidès, Jean-Marie; Baudrillard, Jean; Constant; Donné, Boris; Enzensberger, Hans Magnus; Hardt, Michael; Hecken, Thomas; Heil, Axel; Kaufmann, Vincent; Lentz, Michael; et al. (Basel Utrecht : Centraal Museum Utrecht JRP-Ringier Kunstverlag AG Zürich Museum Tinguely Basel, 2006)
Brau, Jean-Louis ; Chtcheglov, Ivan ; Constant ; Debord, Guy ; Dubuffet, Jean ; Elde, Ansger ; Fischer, Lothar ; Isou, Isidore ; De Jong, Jacqueline ; Jorn, Asger ; Lausen, Uwe ; Pinot-Gallizio, Giuseppe ; Pomerand, Gabriel ; Prem, Heimrad ; Wolman, Gil J. ; Zimmer, Hans-Peter
Engels
boek